PENGARUH MOTIVASI DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT GERAI TERPADU INDONESIA - Yuda Supriatna (CV ODIS, 2021)
PT Gerai Terpadu Indonesia is a national level service company, especially in the field of maintenance services for 3 Kg LPG gas cylinders. From the initial survey, it was known that there were weaknesses in the performance of employees at PT Gerai Terpadu Indonesia as seen from the high absence of employees which could affect company performance. This study aims to analyze whether motivation has a positive and significant effect on employee performance, has a positive and significant effect on employee performance, and analyzes whether motivation and commitment of employees simultaneously have a significant positive effect on employee performance. This research was conducted using multiple linear regression analysis with the help of the SPSS version 20 program. The sample in this study were employees at PT Gerai Terpadu Indonesia. The data research method in this research is using a questionnaire to the entire population of 35 people and data obtained from the company. The results of the percentage descriptive calculation research show that the F test results show F-value = 4.675 with a significance value = 0.016 <0.05, which means that H3 is accepted and H0 is rejected or which means that motivation and commitment of employees together or simultaneously have a positive and significant effect on performance employees. The t-test results of the motivation variable obtained t-value = 2.161 with a significance value = 0.033 <0.05, which means H1 is accepted and H0 is rejected, which means that motivation has a positive and significant effect on employee performance. The t-test results of the employee commitment variable obtained t-value = 2.357 with a significance value = 0.020 <0.05, which means that H2 is accepted and H0 is rejected or which means that employee commitment has a positive and significant effect on employee performance.